Answer :

3,6,9,12, . . .

First term a = 3

Second term t_{1} = 6

Third term t_{2} = 9

Fourth term t_{3} = 12

We know that d = t_{n + 1} – t_{n}

Thus, t_{2} – t_{1} = 9 – 6 = 3

t_{3} – t_{2} = 12 – 9 = 3

Thus, d = 3

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Arithmetic Progression and 'nth' Term of AP55 mins

Sum of n Terms of AP56 mins

Introduction of Geometric Progression60 mins

Imp Qs Practice For Boards (AP)59 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

<span lang="EN-USMHB - Mathematics Part-1

Attempt any five Maharashtra Board - Algebra Papers

Attempt any five Maharashtra Board - Algebra Papers

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1

Attempt any five Maharashtra Board - Algebra Papers

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1